2005
DOI: 10.1002/chem.200500529
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Alkynes Containing α‐Hydrogen Atoms with a Triruthenium Hydrido Carbonyl Cluster: Alkenyl versus Allyl Cluster Derivatives

Abstract: The reactions of the hydrido-triruthenium cluster complex [Ru3(mu-H)(mu3-kappa(2)-HNNMe2)(CO)9] (1; H2NNMe2 = 1,1-dimethylhydrazine) with alkynes that have alpha-hydrogen atoms give trinuclear derivatives containing edge-bridging allyl or face-capping alkenyl ligands. Under mild conditions (THF, 70 degrees C) the isolated products are as follows: [Ru3(mu3-kappa(2)-HNNMe2)(mu-kappa(3)-1-syn-Me-3-anti-EtC3H3)(mu-CO)2(CO)6] (2) and [Ru3(mu3-kappa(2)-HNNMe2)(mu-kappa(3)-1-syn-Me-3-syn-EtC3H3)(mu-CO)2(CO)6] (3) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 57 publications
3
26
1
Order By: Relevance
“…In the context of alkenyl triruthenium complexes, we have recently revised the studies of Hansert and Vahrenkamp4 on the reactivity of the Süss‐Fink's hydrazido‐bridged hydrido carbonyl triruthenium complex [Ru 3 (μ‐H)(μ 3 ‐ κ 2 ‐HNNMe 2 )(CO) 9 ]9 ( 1 ) with terminal and internal alkynes without α‐hydrogen atoms, showing that the products have alkenyl ligands in edge‐bridging or face‐capping positions ( A and B , respectively, in Scheme ) and that the nature of the substituents on the alkyne reagent strongly affects the stability of each product 5. We have also reported that alkynes with α‐hydrogen atoms react with complex 1 to give trinuclear derivatives that contain edge‐bridging allyl ligands ( C and D in Scheme ) 6…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the context of alkenyl triruthenium complexes, we have recently revised the studies of Hansert and Vahrenkamp4 on the reactivity of the Süss‐Fink's hydrazido‐bridged hydrido carbonyl triruthenium complex [Ru 3 (μ‐H)(μ 3 ‐ κ 2 ‐HNNMe 2 )(CO) 9 ]9 ( 1 ) with terminal and internal alkynes without α‐hydrogen atoms, showing that the products have alkenyl ligands in edge‐bridging or face‐capping positions ( A and B , respectively, in Scheme ) and that the nature of the substituents on the alkyne reagent strongly affects the stability of each product 5. We have also reported that alkynes with α‐hydrogen atoms react with complex 1 to give trinuclear derivatives that contain edge‐bridging allyl ligands ( C and D in Scheme ) 6…”
Section: Introductionmentioning
confidence: 97%
“…Alkenyl groups are important ligands in organometallic chemistry because they are invoked in many metal‐mediated transformations of alkynes and alkenes. However, to date, the number of reports dealing with triruthenium carbonyl cluster complexes containing alkenyl ligands is relatively small,1–6 despite the fact that some of these clusters have been recognized as intermediates or as catalyst precursors in alkyne–alkene co‐dimerization7 as well as alkyne hydrogenation,8 dimerization,2b polymerization,2b and hydroformylation2c processes.…”
Section: Introductionmentioning
confidence: 99%
“…In accord with the solid-state structure the aromatic region of the 1 While (2), Os (2) binding of the bridging allyl ligands in these are very similar to those found in 3 and 4, most notably the CeCeC angle of 133.9 (17) and 127(2) in 3 and 4, respectively, are close to those found in the hexanuclear clusters [CeCeC 125.5e128.7 ]. More recently, Cabeza and co-workers have prepared a series of triruthenium clusters with bridging allyl ligands resulting from the insertion of alkynes [32] or conjugated dienes [30,31], including allenes [29] into the metalehydride moiety in [Ru 3 (CO) 9 (m 3 Àk 2 -HNNMe 2 )(m-H)].…”
Section: Resultsmentioning
confidence: 99%
“…We have also reported that alkynes with a-hydrogen atoms react with complex A to give trinuclear derivatives that may contain edge-bridging allyl ligands (D and E in Scheme 1) [6]. In all cases, the nature of the substituents of the alkyne reagent strongly affects the stability of each product and the regioselectivity of the reactions [5,6].…”
Section: Introductionmentioning
confidence: 95%
“…However, to date, the number of reports dealing with triruthenium carbonyl cluster complexes containing alkenyl ligands is relatively small [1][2][3][4][5][6][7][8][9], despite the fact that some of these clusters have been recognized as intermediates or as catalyst precursors for alkyne-alkene codimerization [8] and alkyne hydrogenation [9], dimerization [2b], polymerization [2b] and hydroformylation [2c] processes.…”
Section: Introductionmentioning
confidence: 99%